Optimalisasi Tambak Garam di Desa Bontomanai Kabupaten Pangkep - Nompo, Marwah; Sumarni, Sumarni; Toniasih, Ni Ketut (Jurnal Riset Diwa Bahari (JRDB), 2025)
This study aims to analyze and identify strategies for optimizing salt ponds through the application of modern technology and sustainable management in the coastal areas of Pangkep Regency, especially in Bontomanai Village. The method used in the study is a mixture, or mixed methods with a descriptive analytical approach that aims to describe and analyze the existing conditions of salt ponds and factors that affect the productivity and quality of salt in the field. Data collection techniques used are observation, interviews and questionnaires consisting of two data sources, namely primary and secondary data sources. Meanwhile, the data analysis technique used is descriptive analysis, namely data reduction, data presentation, and drawing conclusions, as well as SWOT analysis. The results of the study indicate that optimizing salt ponds in Bontomanai Village requires an approach that considers local conditions and the potential of available resources. Traditional salt ponds still rely on hereditary methods, but face limitations in efficiency and dependence on the weather. Meanwhile, the application of modern technology has been shown to increase salt productivity and quality, despite facing challenges such as high investment costs and training needs for farmers. Therefore, an approach that combines traditional and modern methods is a more sustainable solution. Integration of technology in certain aspects can increase production efficiency without completely abandoning traditional methods that are more cost-effective and environmentally friendly. With this strategy, optimization of salt ponds can be carried out gradually, improving the welfare of farmers, and strengthening the competitiveness of the salt industry in the area.